Russia and the IMF : The Political Economy of Macro-Stabilization - Hernandez-Cata, Ernesto (IMF Policy Discussion Papers; Policy Discussion Paper ;, 1994)
This paper reviews the experience with macroeconomic stabilization in Russia during the 2 1/2 years following the beginning of reforms in January 1992. It focuses on the different perceptions about the nature, the causes and the consequences of inflation in Russia and about the policies required to deal with it. It recounts the authorities's efforts to control inflation and discusses the major political obstacles to stabilization, including the pressures for subsidized credits, budgetary transfers and tax exemptions and interenterprise arrears. Finally, it examines the role of IMF-supported programs in the process. This is a Paper on Policy Analysis and Assessment and the author(s) would welcome any comments on the present text. Citations should refer to a Paper on Policy Analysis and Assessment of the International Monetary Fund, mentioning the author(s) and the date of issuance. The views expressed are those of the author(s) and do not necessarily represent those of the Fund.